Can’t intubate anaplastic thyroid carcinoma - A case report - Sigdel, B.; Dubey, T.; KC, Neeraj; Nepali, R.; Maharjan, R.; Sah, K.; Upadhyaya, K. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Female, 66 years old with a chief complain of shortness of breath and lump over her neck since 6 month. Neck USG showed enlarged right lobe of thyroid gland with hyperechoic nodules. FNAC confirmed anaplastic carcinoma of thyroid. patient underwent chemotherapy using doxorubicin as agent of choice. She had difficulty in breathing and she kept on high flow of oxygen, even after she had stridor and planned for tracheostomy. MRI revealed heterogeneously enhancing mass (9.6*6.5*10.5 cm) replacing right lobe of thyroid, and extending superiorly till the level carotid bifurcation and inferiorly superior mediastinum. Lesion is partially encasing trachea and laryngeal airway, posteriorly extending into prevertebral space and anteriorly invading strap muscles and sternocleidomastoid muscle. Now it become very difficult stage. She transfers to ICU. intubation tried but failed. As mass was just anterior to trachea and difficult to do tracheostomy without intubation. all hope failed and she put continue to high flow of oxygen.